2019
DOI: 10.1002/path.5209
|View full text |Cite
|
Sign up to set email alerts
|

Disease‐biased and shared characteristics of the immunoglobulin gene repertoires in marginal zone B cell lymphoproliferations

Abstract: The B cell receptor immunoglobulin (Ig) gene repertoires of marginal zone (MZ) lymphoproliferations were analyzed in order to obtain insight into their ontogenetic relationships. Our cohort included cases with MZ lymphomas (n = 488), i.e. splenic (SMZL), nodal (NMZL) and extranodal (ENMZL), as well as provisional entities (n = 76), according to the WHO classification. The most striking Ig gene repertoire skewing was observed in SMZL. However, restrictions were also identified in all other MZ lymphomas studied,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 19 publications
3
14
1
Order By: Relevance
“…In particular, our data are in accordance with previous studies which showed a biased usage of the IGHV genes in favor of IGHV-1- [30]. Conversely, we found an overrepresentation of VH1-2 gene in our cohort of cases (5 out of 28; 17.8%) which has been found mainly in SMZL [30]. VH1-2 is known to react with antigen exposed on apoptotic cells, suggesting that at least a subset of NMZL may arise from a self-antigen antibody producing B cell [6].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In particular, our data are in accordance with previous studies which showed a biased usage of the IGHV genes in favor of IGHV-1- [30]. Conversely, we found an overrepresentation of VH1-2 gene in our cohort of cases (5 out of 28; 17.8%) which has been found mainly in SMZL [30]. VH1-2 is known to react with antigen exposed on apoptotic cells, suggesting that at least a subset of NMZL may arise from a self-antigen antibody producing B cell [6].…”
Section: Discussionsupporting
confidence: 93%
“…Here we show that in NMZL cases, the VH1 family genes were significantly overrepresented compared with transitional B cells, naive B cells, and IgM memory B cells [29]. In particular, our data are in accordance with previous studies which showed a biased usage of the IGHV genes in favor of IGHV-1- [30]. Conversely, we found an overrepresentation of VH1-2 gene in our cohort of cases (5 out of 28; 17.8%) which has been found mainly in SMZL [30].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…IMGT/V-QUEST is frequently used by clinicians for the analysis of the somatic hypermutations in leukemia, lymphoma and myeloma, and more particularly in chronic lymphocytic leukemia (CLL) [ 291 , 292 , 293 ] in which the percentage of mutations in the patient VH has a prognostic value. The sequences of the V-(D)-J junctions determined by IMGT/JunctionAnalysis are also used in the characterization of stereotypic patterns in CLL and B cell lymphoproliferations [ 291 , 292 , 293 , 294 ] and for the junction synthesis of specific probes for the follow-up of residual diseases in leukemias and lymphomas.…”
Section: Imgt ® Databases and Tools For Ig Sequmentioning
confidence: 99%